Multifaceted peptide assisted one-pot synthesis of gold nanoparticles for plectin-1 targeted gemcitabine delivery in pancreatic cancer. Issue 40 (9th October 2017) - Pal, Krishnendu; Al-suraih, Farah; Gonzalez-Rodriguez, Roberto; Dutta, Shamit Kumar; Wang, Enfeng; Kwak, H. Shaun; Caulfield, Thomas R.; Coffer, Jeffery L.; Bhattacharya, Santanu
Abstract : Tumor-selective uptake of plectin-1 targeting peptide-modified gold nanoparticles ameliorates targeted delivery of gemcitabine in pancreatic ductal adenocarcinoma. Abstract : An astute modification of the plectin-1-targeting peptide KTLLPTP by introducing a C-terminal cysteine preceded by a tyrosine residue imparted a reducing property to the peptide. This novel property is then exploited to fabricate gold nanoparticles (GNP) via an in situ reduction of gold(iii ) chloride in a one-pot, green synthesis. The modified peptide KTLLPTPYC also acts as a template to generate highly monodispersed, spherical GNPs with a narrow size distribution and improved stability. Plectin-1 is known to be aberrantly expressed in the surface of pancreatic ductal adenocarcinoma (PDAC) cells while showing cytoplasmic expression in normal cells. The synthesized GNPs are thus in situ surface modified with the peptides via the cysteine residue leaving the N-terminal KTLLPTP sequence free for targeting plectin-1. The visual molecular dynamics based simulations support the experimental observations like particle size, gemcitabine conjugation and architecture of the peptide-grafted nanoassembly. Additionally, GNPs conjugated to gemcitabine demonstrate significantly higher cytotoxicity in vitro in two established PDAC cell lines (AsPC-1 and PANC-1) and an admirable in vivo antitumor efficacy in a PANC-1 orthotopic xenograft model through selective uptake in PDAC tumor tissues. Altogether, this strategy represents a unique method for the fabrication of a GNP based targeted drug delivery platform using a multifaceted peptide that acts as reducing agent, template for GNP synthesis and targeting agent to display remarkable selectivity towards PDAC.